Electrolyte, secondary battery, and device
By adding specific additives to the electrolyte of lithium-ion batteries to form an insulating film, the problem of exothermic reaction of lithium-ion batteries when overcharged is solved, and its safety performance and cycle performance are significantly improved.
Patent Information
- Application Number
- CN202310871357.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
AI Technical Summary
Lithium-ion batteries are prone to severe exothermic reactions when over-abuse, resulting in swelling, explosion or fire, affecting their safety performance and circulation performance.
The first additive (benzene ring compound), the second additive (biphenyl compound) and the third additive (organosilicon compound) are added to the electrolyte to form an insulating film on the surface of the electrode plate to suppress voltage increase and electrolysis The oxidative decomposition of the liquid improves the safety performance and cycle performance of the battery.
Through the effect of gradient polymerization, the voltage increase is effectively suppressed, the electrolyte is prevented from decomposing under high pressure, side reactions are reduced, and the safety performance and cycle performance of the battery are improved.
Smart Images

Figure CN119315106A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to an electrolyte, a secondary battery and a device. Background Art
[0002] Among commercial rechargeable batteries, lithium-ion batteries have higher energy density and wider operating voltage, and are widely used in electric vehicles, digital 3C, energy storage and other fields. The cost, life, safety and other characteristics of lithium-ion batteries have always been the focus of researchers. Safety performance, cycle performance and calendar life are the key to whether lithium-ion batteries can be used in electric vehicles.
[0003] As we all know, when over-abused, lithium-ion batteries will have severe exothermic reactions (such as oxidative decomposition and combustion of the electrolyte), which can easily cause swelling or even explosion and fire. Overcharging is a type of battery abuse. Overcharging can cause heating problems in the early stages of the battery. The increase in battery temperature will increase the reactivity of the electrode plates and the electrolyte, accelerate the decomposition of the electrolyte and the occurrence of side reactions, thereby increasing the amount of heat released. The accumulation of heat will further deteriorate battery safety. Further temperature increases will also directly affect the structural integrity of the binder in the diaphragm and the positive and negative electrode plates, which will directly lead to battery loss of control, and may eventually cause serious dangers such as fire and explosion. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present application provides an electrolyte, a secondary battery and a device. The present application can protect the electrode plate by adding a first additive, a second additive and a third additive to the electrolyte, reduce the side reaction between the electrode plate and the electrolyte, reduce gas production, and improve the safety performance and cycle performance of the secondary battery; further, the first additive and the second additive can also oxidize and polymerize when the secondary battery is overcharged to avoid thermal runaway.
[0005] The first aspect of the present application provides an electrolyte, which includes a lithium salt, a non-aqueous solvent, a first additive as shown in Formula 1, a second additive as shown in Formula 2, and a third additive as shown in Formula 3;
[0006]
[0007] In Formula 1, R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, cyano or halogen;
[0008] In Formula 2, R3, R4, R5, R6, R7, and R8 are each independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, cyano, or halogen;
[0009] In formula 3, R9, R10 , R 11 and R 12 are each independently selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl or substituted or unsubstituted C2-C6 alkynyl, wherein R9, R 10 , R 11 and R 12 At least one of them is selected from substituted or unsubstituted C2-C6 alkenyl or substituted or unsubstituted C2-C6 alkynyl;
[0010] The substituted substituents are each independently selected from cyano and / or halogen.
[0011] A second aspect of the present application provides a secondary battery, comprising a first electrode plate, a second electrode plate and the aforementioned electrolyte.
[0012] A third aspect of the present application provides a device, which includes the aforementioned secondary battery.
[0013] The technical solution of this application can achieve the following beneficial effects:
[0014] The first additive provided in the present application is a benzene ring compound, the second additive is a biphenyl compound, and the third additive is an organosilicon compound. The first additive and the second additive have different oxidation potentials. When the two are added to the electrolyte in combination, when the battery is overcharged, the one with the lower oxidation potential will preferentially lose electrons and undergo oxidative polymerization by dehydrogenation, forming a layer of mesh polymer film attached to the surface of the electrode plate. The film has insulating properties, and a large amount of charge will be consumed during the oxidative polymerization reaction, which will eventually suppress the increase in voltage; if the potential continues to rise to a higher oxidation potential, the one with the higher oxidation potential will then undergo oxidative polymerization to form a denser polymer film, and the polymer film finally formed has higher insulation, further suppressing the increase in voltage; thus, as the voltage increases, the effect of gradient polymerization is achieved, the increase in voltage is more effectively suppressed, and the electrolyte is prevented from decomposing under high voltage. At the same time, it can also avoid the accumulation of heat inside the battery due to high voltage, thereby avoiding damage to the electrode plate and improving the safety characteristics of the battery. In addition, since the first additive and the second additive have higher oxidation potentials, oxidative polymerization will not occur during the normal formation and circulation of the lithium battery, so it will not have a negative effect on the performance of the battery. In addition, the third additive can form a film on the surface of the electrode plate during the chemical composition stage, and the formed solid electrolyte interface film can improve the contact safety between the electrode plate and the electrolyte, slow down the occurrence of side reactions in the electrolyte, thereby significantly improving the flatulence problem of the lithium battery during overcharging, thereby improving the high temperature performance of the lithium battery; and, in the early stage of battery overcharge abuse, the heat generated at the electrode plate will surge, but because the voltage has not reached the oxidation potential of the first additive or the second additive, at this time, the first additive and the second additive cannot play a role, and the third additive can form a dense and uniform three-dimensional interface film on the surface of the positive electrode plate, which can effectively isolate the contact between the electrode plate and the electrolyte, reduce side reactions, thereby improving the high temperature performance of the battery cell, slowing down the occurrence of thermal runaway and the hazards of thermal runaway. In summary, by adding the above-mentioned substance combination into the electrolyte system, the first additive, the second additive and the third additive can form a synergistic effect. On the one hand, they can form a dense solid electrolyte interface film on the surface of the electrode plate during the lithium battery capacity formation stage, reducing the contact between the electrolyte and the electrode plate to avoid the decomposition of the electrolyte under high voltage. On the other hand, when the lithium battery is overcharged, oxidative polymerization can occur, forming an insulating film on the surface of the electrode plate, while consuming excess charge, inhibiting the increase in voltage and the oxidative decomposition of the electrolyte, and improving the safety performance of the battery. Based on the above improvements, the electrolyte of the present application has excellent cycle performance, storage performance and safety performance at high temperatures when used in secondary batteries. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0016] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0017] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0018] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0019] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0020] The term "silicon-based material" is not particularly limited, as long as the material contains silicon. In the present application, the "silicon-based material" may be silicon, silicon alloys, silicon-oxygen compounds, silicon-carbon compounds, and any mixture of the above silicon-based materials.
[0021] The term "carbon-based material" is not particularly limited, and may be graphite, soft carbon, hard carbon, carbon nanotubes, graphene, and any mixture of the above carbon-based materials. The term "graphite" is not particularly limited, and may be artificial graphite and / or natural graphite.
[0022] The term "C1-C6 alkyl" includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, and the like.
[0023] The term "C1-C6 alkoxy" includes, but is not limited to, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, isopentyloxy or n-hexyloxy, etc.
[0024] The term "C2-C6 alkenyl" includes, but is not limited to, ethenyl, propenyl, butenyl, pentenyl or hexenyl and the like.
[0025] The term "C2-C6 alkynyl" includes, but is not limited to, ethynyl, propynyl, butynyl, pentynyl or hexynyl and the like.
[0026] The term "substituted or unsubstituted" means that the functional group recorded after the term may or may not have a substituent. For example, "substituted or unsubstituted C1-C6 alkyl" refers to a C1-C6 alkyl with a substituent or an unsubstituted C1-C6 alkyl. The number of substituents may be 1 or more than 2, and the substituents include at least one of halogen, alkyl, aryl, heteroaryl or cyano. It should be understood that when the number of substituents is greater than 1, each substituent may be the same or different.
[0027] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0028] 1. Electrolyte
[0029] One or more embodiments of the present application provide an electrolyte, the electrolyte comprising a lithium salt, a non-aqueous solvent, a first additive as shown in Formula 1, a second additive as shown in Formula 2, and a third additive as shown in Formula 3;
[0030]
[0031]
[0032] In Formula 1, R1 and R3 are each independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, cyano or halogen; in Formula 2, R3, R4, R5, R6, R7, and R8 are each independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, cyano or halogen, wherein R9, R 10 , R 11 and R 12At least one of them is selected from substituted or unsubstituted C2-C6 alkenyl or substituted or unsubstituted C2-C6 alkynyl; in Formula 3, R9, R 10 , R 11 and R 12 Each is independently selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl; the substituted substituents are each independently selected from cyano and / or halogen.
[0033] The first additive provided in the present application is a benzene ring compound, the second additive is a biphenyl compound, and the third additive is an organosilicon compound. The first additive and the second additive have different oxidation potentials. When the two are added to the electrolyte in combination, when the battery is overcharged, the one with the lower oxidation potential will preferentially lose electrons and undergo oxidative polymerization by dehydrogenation, forming a layer of mesh polymer film attached to the surface of the electrode plate. The film has insulating properties, and a large amount of charge will be consumed during the oxidative polymerization reaction, which will eventually suppress the increase in voltage; if the potential continues to rise to a higher oxidation potential, the one with the higher oxidation potential will then undergo oxidative polymerization to form a denser polymer film, and the polymer film finally formed has higher insulation, further suppressing the increase in voltage; thus, as the voltage increases, the effect of gradient polymerization is achieved, the increase in voltage is more effectively suppressed, and the electrolyte is prevented from decomposing under high voltage. At the same time, it can also avoid the accumulation of heat inside the battery due to high voltage, thereby avoiding damage to the electrode plate and improving the safety characteristics of the battery. In addition, since the first additive and the second additive have higher oxidation potentials, oxidative polymerization will not occur during the normal formation and circulation of the lithium battery, so it will not have a negative effect on the performance of the battery. In addition, part of the third additive can form a film on the surface of the electrode plate during the chemical composition stage, and the formed solid electrolyte interface film can improve the contact safety between the electrode plate and the electrolyte, slow down the occurrence of side reactions in the electrolyte, thereby significantly improving the flatulence problem of the lithium battery during overcharging, and thus improving the high temperature performance of the lithium battery; and, in the early stage of battery overcharge and abuse, the heat generated at the electrode plate will surge, but because the voltage has not reached the oxidation potential of the first additive or the second additive, at this time, the first additive and the second additive cannot play a role, and the remaining third additive can form a dense and uniform three-dimensional interface film on the surface of the positive electrode plate, which can effectively isolate the contact between the electrode plate and the electrolyte, reduce side reactions, thereby improving the high temperature performance of the battery cell, and slowing down the occurrence of thermal runaway and the hazards of thermal runaway. In summary, by adding the above-mentioned substance combination into the electrolyte system, the first additive, the second additive and the third additive can form a synergistic effect. On the one hand, they can form a dense solid electrolyte interface film on the surface of the electrode plate during the lithium battery formation stage, reducing the contact between the electrolyte and the electrode plate to avoid decomposition of the electrolyte under high voltage. On the other hand, they can undergo oxidative polymerization when the lithium battery is overcharged to form an insulating film on the surface of the electrode plate, while consuming excess charge, inhibiting the voltage increase and oxidative decomposition of the electrolyte, and improving the safety performance of the battery.
[0034] In some embodiments, in Formula 1, R1 is selected from substituted or unsubstituted C1-C4 alkyl, cyano or fluorine, and R2 is selected from substituted or unsubstituted C1-C4 alkyl, wherein the substituted substituents are each independently selected from fluorine.
[0035] In some embodiments, in Formula 2, R3, R4 and R5 are each independently selected from hydrogen, substituted or unsubstituted C1-C4 alkyl, cyano or fluorine, and R6, R7 and R8 are each independently selected from hydrogen, substituted or unsubstituted C1-C4 alkyl, or fluorine. Wherein, the substituted substituents are each independently selected from fluorine.
[0036] In some embodiments, in Formula 3, R9, R 10 and R 11 are each independently selected from substituted or unsubstituted C2-C3 alkenyl, substituted or unsubstituted C2-C3 alkynyl, R 12 is selected from substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C2-C3 alkenyl or substituted or unsubstituted C2-C3 alkynyl, wherein the substituted substituents are each independently selected from fluorine.
[0037] In some embodiments, the first additive is selected from at least one of the following compounds:
[0038]
[0039] In some embodiments, the second additive is selected from at least one of the following compounds:
[0040]
[0041]
[0042] In some embodiments, the third additive contains unsaturated bonds, which enable it to have the ability to copolymerize, and then each molecular chain has the ability to cross-link into a film. As a result, the third additive can form a dense and uniform three-dimensional interface film on the surface of the positive electrode plate, which can effectively isolate the contact between the electrode plate and the electrolyte, reduce side reactions, thereby improving the high temperature performance of the battery cell, and reducing the occurrence of thermal runaway and the hazard of thermal runaway. In some embodiments, the third additive is selected from at least one of the following compounds:
[0043] (tetravinylsilane, TVS),
[0044] In some embodiments, the first additive is
[0045] In some embodiments, the second additive is
[0046] In some embodiments, the third additive is
[0047] In some embodiments, the first additive is The second additive is The third additive is
[0048]
[0049] In some embodiments, the first additive is The second additive is The third additive is
[0050] In some embodiments, the first additive is The second additive is The third additive is
[0051] In some embodiments, the first additive is The second additive is The third additive is
[0052] In some embodiments, based on the mass of the electrolyte, the mass percentage of the first additive is 1% to 5%. Exemplarily, the mass percentage of the first additive is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range consisting of any two of the above values. In some embodiments, based on the mass of the electrolyte, the mass percentage of the first additive is 2% to 4%.
[0053] In some embodiments, based on the mass of the electrolyte, the mass percentage of the second additive is 1% to 5%. Exemplarily, the mass percentage of the second additive is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range consisting of any two of the above values. In some embodiments, based on the mass of the electrolyte, the mass percentage of the second additive is 2% to 4%.
[0054] In some embodiments, based on the mass of the electrolyte, the mass percentage of the third additive is 0.5% to 3%. Exemplarily, the mass percentage of the third additive is 0.5%, 0.7%, 1%, 1.3%, 1.5%, 1.7%, 2%, 2.3%, 2.5%, 2.7%, 3%, or a range consisting of any two of the above values. In some embodiments, based on the mass of the electrolyte, the mass percentage of the third additive is 1% to 2%.
[0055] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide (LiFNFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluoromalonate)borate (LiBFMB), lithium 4,5-dicyano-2-(trifluoromethyl)imidazolium (LiTDI), and lithium difluorooxalatoborate (LiDFOB).
[0056] In some embodiments, the concentration of the lithium salt is 0.5 mol / L to 1.5 mol / L. The concentration of the lithium salt is 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L or a range consisting of any two of the above values.
[0057] In some embodiments, the non-aqueous solvent includes at least one of a linear carbonate, a cyclic carbonate or a carboxylic acid ester; wherein the linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate; the cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate, and butylene carbonate; the carboxylic acid ester is selected from at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and butyl propionate.
[0058] In some embodiments, the mass percentage of the non-aqueous solvent is 50% to 90% based on the mass of the electrolyte. Exemplarily, the mass percentage of the non-aqueous solvent is 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or a range consisting of any two of the above values based on the mass of the electrolyte.
[0059] 2. Secondary battery
[0060] One or more embodiments of the present application further provide a secondary battery, which includes the electrolyte in the aforementioned embodiment.
[0061] In some embodiments, the secondary battery of the present application further includes a first electrode plate and a second electrode plate. The first electrode plate may be a positive electrode plate or a negative electrode plate. The second electrode plate may also be a positive electrode plate or a negative electrode plate. The first electrode plate and the second electrode plate may be the same or different, and the present application does not impose any specific restrictions on this.
[0062] In the following, the secondary battery of the present application is further explained by taking the first electrode plate as a positive electrode plate and the second electrode plate as a negative electrode plate as an example.
[0063] In some embodiments, the first electrode plate includes a first current collector and a first active material layer located on a surface of the first current collector.
[0064] In some embodiments, the first current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.
[0065] In some embodiments, the first active material layer includes a first active material.
[0066] In some embodiments, the first active material includes at least one of a nickel-cobalt-based ternary material and a phosphate-based material.
[0067] In some embodiments, the nickel-cobalt ternary material includes LiNi x Co y M (1-x-y) At least one of the O2 materials, M includes at least one of manganese, aluminum, magnesium, chromium, calcium, zirconium, molybdenum, silver or niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1. In some embodiments, x is 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or a range consisting of any two of the above values; y is 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or a range consisting of any two of the above values. Specifically, 0.8≤x≤1, 0≤y≤0.2, x+y≤1. In some embodiments, the nickel-cobalt ternary material includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92 or Ni95.
[0068] In some embodiments, the phosphate-based material includes LiMn k B (1-k) PO4, wherein 0≤k≤1, and the B element is selected from at least one of iron, cobalt, magnesium, calcium, zinc, chromium, or lead. In some embodiments, k is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or a range consisting of any two of the above values. In some embodiments, the phosphate-based material includes lithium iron phosphate, LiMn 0.6 Fe 0.4 PO4 or LiMn 0.8 Fe 0.2 At least one of PO4.
[0069] In some embodiments, the first active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate.
[0070] In some embodiments, the first active material layer may further include a binder, and optionally a conductive agent. The binder improves the bonding between the first active material particles and also improves the bonding between the first active material and the first current collector.
[0071] In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0072] In some embodiments, the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material includes natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material includes metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0073] In a specific example of the present application, the first active material, the conductive agent, and the binder are fully stirred and mixed in an N-methylpyrrolidone solvent system in a certain proportion, and then coated on an aluminum current collector, dried, and rolled to obtain a first electrode plate. It is understood that the aforementioned solvent system and current collector material are only used as an example and are not intended to limit the present application. The solvent system and current collector material of the present application can be any combination conventionally selected in the art.
[0074] In some embodiments, the second electrode sheet includes a second current collector and a second active material layer located on a surface of the second current collector.
[0075] In some embodiments, the second current collector may include copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0076] In some embodiments, the second active material layer includes a second active material.
[0077] In some embodiments, the second active material includes a silicon-based material, or a mixture of a silicon-based material and at least one material selected from a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium. The silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound, and a silicon-carbon compound. The carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene. The tin-based material includes at least one of tin, tin oxide, and a tin alloy. The phosphorus-based material includes phosphorus and / or a phosphorus-carbon composite.
[0078] In some embodiments, based on the mass of the second active material, the mass percentage of the silicon-based material is 10% to 100%. Exemplarily, the mass percentage of the silicon-based material is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or a range consisting of any two of the above values.
[0079] In some embodiments, the second active material layer may further include a binder and a conductive agent.
[0080] In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0081] In some embodiments, the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0082] In a specific example of the present application, the second active material, the conductive agent, and the binder are fully stirred and mixed in an N-methylpyrrolidone solvent system in a certain proportion, and then coated on an aluminum current collector, dried, and rolled to obtain a second electrode sheet. It is understood that the aforementioned solvent system and current collector material are only used as an example and are not intended to limit the present application. The solvent system and current collector material of the present application can be any combination conventionally selected in the art.
[0083] In some embodiments of the present application, the secondary battery further includes a diaphragm, which is located between the first electrode plate and the second electrode plate to prevent short circuit. The present application embodiment does not impose any specific restrictions on the material and shape of the diaphragm, which can be any technology disclosed in the prior art.
[0084] In some embodiments, the diaphragm includes a polymer or inorganic substance formed by a material that is stable to the electrolyte of the present application. For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected. A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance.
[0085] In some implementations, the inorganic layer includes inorganic particles and a binder, and the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0086] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0087] 3. Battery Module
[0088] One or more embodiments of the present application further provide a battery module, the battery module comprising the aforementioned secondary battery.
[0089] The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be one or more, and the specific number can be adjusted according to the application and capacity of the battery module.
[0090] 4. Battery Pack
[0091] One or more embodiments of the present application also provide a battery pack, which includes the aforementioned battery module.
[0092] The number of battery modules contained in a battery pack may be one or more, and the specific number may be adjusted according to the application and capacity of the battery pack.
[0093] 5. Device
[0094] One or more embodiments of the present application also provide a device, which includes at least one of the aforementioned secondary battery, battery module and battery pack.
[0095] In some embodiments, the devices of the present application include but are not limited to: laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries or lithium-ion capacitors, etc.
[0096] The technical solution of the present application will be further illustrated below with reference to specific embodiments and comparative examples.
[0097] Examples and Comparative Examples
[0098] Example 1
[0099] Preparation of electrolyte: In an argon-protected glove box (water content <1ppm, oxygen content <1ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of 30:70. 4% of the first additive 1-1, 4% of the second additive 2-1 and 3% of the third additive 3-1 were added to the total mass of the electrolyte. Then, lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1.2 mol / L, and the electrolyte of Example 1 was obtained after stirring evenly.
[0100] Preparation of positive electrode sheet: LiNi 0.9 Co 0.05 Mn 0.05 O2, conductive agent carbon nanotube / acetylene black, binder polyvinylidene fluoride PVDF, by weight proportion LiNi 0.9 Co 0.05 Mn o.05O2: (CNT / acetylene black): PVDF = 95: (2 / 1): 2 was fully slurried in an N-methylpyrrolidone solvent system, coated on a 12 μm thick aluminum-coated current collector, dried, and roll-pressed to obtain a positive electrode sheet.
[0101] Preparation of negative electrode sheet: negative electrode active materials: artificial graphite, silicon-oxygen (SiO x ), conductive agent acetylene black, binder styrene butadiene rubber, thickener sodium carboxymethyl cellulose, and polyacrylic acid are fully slurried in a deionized water solvent in a weight ratio of 85:10:2:1.5:1:0.5, coated on a 8μm thick copper current collector, dried, and rolled to obtain a negative electrode sheet.
[0102] Diaphragm: Use polyethylene diaphragm.
[0103] Preparation of lithium-ion battery: The positive electrode plate, separator and negative electrode plate are stacked in Z-shape in sequence, and the obtained bare battery cell is placed in a punched aluminum-plastic film soft package shell. After drying, non-aqueous electrolyte is injected, and after standing, forming, aging, degassing, shaping and other processes, a lithium-ion battery is finally obtained.
[0104] Examples 2 to 22 and Comparative Examples 1 to 11
[0105] Examples 2 to 22 and Comparative Examples 1 to 11 are achieved by adjusting the type and content of additives in the electrolyte on the basis of Example 1. Specific adjustment measures and detailed data are shown in Table 1.
[0106] Test Method
[0107] 1. Oxidation potential test
[0108] The positive electrode half-cell was assembled for LSV (linear voltammetric sweep test), the positive electrode was made of high-nickel ternary material, the negative electrode was made of lithium metal, the scanning voltage range was 0-6V, and the scanning rate was 1mV / s. The oxidation potential window of the electrolyte containing different combination additives obtained in different embodiments and comparative examples for the high-nickel positive electrode was tested.
[0109] 2. Cycle capacity retention rate
[0110] Place the lithium-ion battery in an environment of 25°C, charge it to 4.25V with constant current and constant voltage, with a cut-off current of 0.01C, and then discharge it to 3V with constant current. Calculate the capacity retention rate after 500 cycles. The calculation formula is as follows:
[0111] Capacity retention rate (%) = discharge capacity after N cycles / initial discharge capacity × 100%.
[0112] 3. Overcharge test
[0113] Place the battery after formation and capacity separation in a constant temperature box at 25°C and charge it to 200% SOC at a constant current of 1C. If thermal runaway occurs during the process, terminate the test; if not, continue the test.
[0114] 4. Thickness change rate test
[0115] During the overcharge test, use a micrometer to mark the change in battery thickness at all times and calculate the thickness change rate. The calculation formula is as follows:
[0116] Thickness change rate (%) = thickness of lithium-ion battery before thermal runaway / thickness of lithium-ion battery before overcharging.
[0117] 5. Impedance (DCR) growth rate test
[0118] The lithium-ion battery involved in the cycle capacity retention test was subjected to a 50% SOC DCR test before and after the cycle. At 50% SOC, the battery was discharged at 2C current for 10 seconds, and the DCR in this state was recorded.
[0119] Impedance growth rate after cycle (%) = 50% SOC DCR after cycle / 50% SOC DCR before cycle × 100%.
[0120] Referring to Table 1, Examples 1 to 22 respectively added different combinations of the first additive, the second additive and the third additive to the electrolyte. Compared with Comparative Example 1 in which no above-mentioned compounds are added, the oxidation potential, thickness change and impedance change of the lithium-ion batteries of Examples 1 to 22 are significantly improved, the overcharge gain effect is significantly improved, and the capacity retention rate is not deteriorated. In combination with Comparative Examples 2 to 4, it can be seen that when only any one of the first additive, the second additive and the third additive is added, the overcharge gain effect is not obvious. In combination with Comparative Example 5, it can be seen that when the first additive and the second additive are used without the third additive, the overcharge gain effect is reduced, the impedance change is not obvious, and the thickness change is more obvious. In combination with Comparative Examples 7 and 8, the overcharge gain effect is not obvious when only the first additive and the third additive are used, or when the second additive and the third additive are used. In combination with Comparative Example 10, when the content of the third additive is low, the thickness change is significantly deteriorated. It can be seen that the synergistic effect between the three compounds is obvious. Further, in combination with Comparative Examples 8, 9 and 11, when any one of the first additive, the second additive and the third additive is excessive, the overcharge gain effect is improved, but the capacity retention rate, impedance change, and thickness change after the cycle are significantly deteriorated. This is because the three additives are all non-lithium-conductive substances. During the cycle, the consumption of the additives after polymerization will cause a significant change in impedance. Therefore, it is necessary to use them reasonably and control the dosage.
[0121] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
[0122]
[0123]
[0124]
[0125]
[0126]
[0127]
[0128]
[0129]
Claims
1. An electrolyte, characterized in that: include: A lithium salt, a non-aqueous solvent, a first additive as shown in Formula 1, a second additive as shown in Formula 2, and a third additive as shown in Formula 3; In Formula 1, R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, cyano or halogen; In Formula 2, R3, R4, R5, R6, R7, and R8 are each independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, cyano, or halogen; In formula 3, R9, R 10 , R 11 and R 12 are each independently selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl or substituted or unsubstituted C2-C6 alkynyl, wherein R9, R 10 , R 11 and R 12 At least one of them is selected from substituted or unsubstituted C2-C6 alkenyl or substituted or unsubstituted C2-C6 alkynyl; The substituted substituents are each independently selected from cyano and / or halogen.
2. The electrolyte according to claim 1, characterized in that The electrolyte satisfies at least one of the following conditions: (a) In formula 1, R1 is selected from substituted or unsubstituted C1-C4 alkyl, cyano or fluorine, and R2 is selected from substituted or unsubstituted C1-C4 alkyl; (b) In formula 2, R3, R4 and R5 are each independently selected from hydrogen, substituted or unsubstituted C1-C4 alkyl, cyano or fluorine, and R6, R7 and R8 are each independently selected from hydrogen, substituted or unsubstituted C1-C4 alkyl, or fluorine; (c) In formula 3, R9, R 10 and R 11 are each independently selected from substituted or unsubstituted C2-C3 alkenyl, substituted or unsubstituted C2-C3 alkynyl, R 12 is selected from substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C2-C3 alkenyl or substituted or unsubstituted C2-C3 alkynyl; (d) The substituents of the substitution are each independently selected from fluorine.
3. The electrolyte according to claim 2, characterized in that The electrolyte also satisfies at least one of the following conditions: (e) The first additive is selected from at least one of the following compounds: (f) the second additive is selected from at least one of the following compounds: (g) The third additive is selected from at least one of the following compounds:
4. The electrolyte according to any one of claims 1 to 3, characterized in that The electrolyte also satisfies at least one of the following conditions: (h) the first additive is 1-3 or 1-7; (i) the second additive is (j) The third additive is 5. The electrolyte according to claim 4, characterized in that The first additive is The second additive is The third additive is 6. The electrolyte according to any one of claims 1 to 3, characterized in that The electrolyte also satisfies at least one of the following conditions: (k) based on the mass of the electrolyte, the mass percentage of the first additive is 1% to 5%; (l) based on the mass of the electrolyte, the mass percentage of the second additive is 1% to 5%; (m) Based on the mass of the electrolyte, the mass percentage of the third additive is 0.5% to 3%.
7. The electrolyte according to claim 6, characterized in that The electrolyte also satisfies at least one of the following conditions: (n) based on the mass of the electrolyte, the mass percentage of the first additive is 2% to 4%; (o) based on the mass of the electrolyte, the mass percentage of the second additive is 2% to 4%; (p) Based on the mass of the electrolyte, the mass percentage of the third additive is 1% to 2%.
8. The electrolyte according to any one of claims 1 to 3, characterized in that The electrolyte also satisfies at least one of the following conditions: (q) the lithium salt comprises at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate), lithium bis(fluoromalonate)borate, lithium 4,5-dicyano-2-(trifluoromethyl)imidazolium or lithium difluorooxalatoborate; the concentration of the lithium salt is 0.5 mol / L to 1.5 mol / L; (r) the non-aqueous solvent comprises at least one of a linear carbonate, a cyclic carbonate or a carboxylic acid ester; wherein the linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate; the cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate and butylene carbonate; the carboxylic acid ester is selected from at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and butyl propionate; and the mass percentage of the non-aqueous solvent is 50% to 90% based on the mass of the electrolyte.
9. A secondary battery, characterized in that: include: A first electrode sheet, a second electrode sheet, and an electrolyte as claimed in any one of claims 1 to 8.
10. The secondary battery according to claim 9, characterized in that: The secondary battery satisfies at least one of the following conditions: (s) The first electrode plate includes a first active material layer, wherein the first active material of the first active material layer includes at least one of a nickel-cobalt ternary material and a phosphate-based material; the nickel-cobalt ternary material includes LiNi x Co y M (1-x-y) At least one of the O2 materials, M includes at least one of manganese, aluminum, magnesium, chromium, calcium, zirconium, molybdenum, silver or niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1; the phosphate material includes LiMn k B (1-k) PO4, 0≤k≤1, and the B element includes at least one of iron, cobalt, magnesium, calcium, zinc, chromium or lead; (t) The second electrode plate includes a second active material layer, and the second active material of the second active material layer includes a silicon-based material, or a mixture of a silicon-based material and at least one material selected from a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium; the silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound, and a silicon-carbon compound; the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene; the tin-based material includes at least one of tin, tin oxide, and a tin alloy; the phosphorus-based material includes phosphorus and / or a phosphorus-carbon complex; based on the mass of the second active material, the mass percentage of the silicon-based material is 10% to 100%.
11. A device, characterized in that: A secondary battery comprising the secondary battery according to claim 9 or 10.